High Power Distance Enhances Employees' Preference for Likable Managers: A Resource Dependency Perspective - Wei, Cong; Sun, Xiaomin; Liu, Jia; Zhou, Chunfang; Xue, Gang (Frontiers in Psychology, 2017)
Is a manager’s likability important from an employee’s perspective? Research results in this field are scant and inconsistent. The current study explored employees’ response to managers’ likability and the moderating effect of power distance at both the cultural and individual levels. In study 1, following the countercultural priming experimental paradigm proposed by Van den Bos et al. (2013), 121 college students from China (a high power distance culture) and 99 college students from Denmark (a low power distance culture) were randomly assigned to either a countercultural (experimental) condition or a control condition. All participants were required to complete a manager selection task using the zero-acquaintance paradigm to measure their preference for likable managers. The results confirmed the moderating role of power distance at the cultural level. Study 2 further explored the moderating effect of power distance orientation at the individual level, as well as the boundary condition of the degree of resource dependence from the employee’s perspective. One hundred and three Chinese participants with work experience were randomly assigned to either the subordinate perspective (high resource dependence) or the HR department perspective (low resource dependence) condition and completed the same task as in study 1. The results suggested that high power distance-oriented participants demonstrate stronger preference for likable manager candidates than do low power distance-oriented participants. In addition, these findings hold only when employees expect a high resource dependence relation with the manager. Theoretical and practical implications of the research findings and future research directions were discussed.